The histological slides and drawings of Cajal - Garcia-Lopez, Pablo; Garcia-Marin, Virginia; Freire, Miguel (Frontiers in Neuroanatomy, 2010)
Ramon y Cajal´s studies in the world of neuroscience provoked a radical change in the course of its history. For this reason he is considered as the father of modern neuroscience. Some of his items are housed at the Cajal Museum (Cajal Institute, CSIC, Madrid, Spain). In this article, we will present an analysis of Cajal’s effects used in his research that could help to understand his enormous scientific production, and that offers some curious insights into his work and his legacy. Furthermore, we present some images relating Cajal’s scientific drawings with his histological slides.